Comparative Analysis of Container Orchestration Platforms: Kubernetes vs. Docker Swarm (International Journal of Scientific Research in Science and Technology, 2024)
Novel software architecture patterns, including microservices, have surfaced in the last ten years to increase the modularity of applications and to simplify their development, testing, scaling, and component replacement. In response to these emerging trends, new approaches such as DevOps methods and technologies have arisen to facilitate automation and monitoring across the whole software construction lifecycle, fostering improved collaboration between software development and operations teams. The resource management (RM) strategies of Kubernetes and Docker Swarm, two well-known container orchestration technologies, are compared in this article. The main distinctions between RM, scheduling, and scalability are examined, with an emphasis on Kubernetes’ flexibility and granularity in contrast to Docker Swarm’s simplicity and use. In this article, a case study comparing the performance of two popular container orchestrators—Kubernetes and Docker Swarm—over a Web application built using the microservices architecture is presented. By raising the number of users, we compare how well Docker Swarm and Kubernetes perform under stress. This study aims to provide academics and practitioners with an understanding of how well Docker Swarm and Kubernetes function in systems built using the suggested microservice architecture. The authors’ Web application is a kind of loyalty program, meaning that it offers a free item upon reaching a certain quantity of purchases. According to the study’s findings, Docker Swarm outperforms Kubernetes in terms of efficiency as user counts rise.